Ag nanodot array as a platform for surface-enhanced Raman scattering - Jung, Mi; Kim, Seung Kyu; Lee, Seok; Kim, Jae Hun; Woo, Deok Ha (SPIE-SOC PHOTO-OPTICAL INSTRUMENTATION ENGINEERS, 2013)
Well-ordered Ag nanodot array on indium-tin-oxide (ITO) glass is adopted as a sensor platform based on surface-enhanced Raman scattering (SERS). SERS has attracted extensive attention in the development of sensitive chemical or biological sensors due to its property of the amplification of electromagnetic fields on a metal nanostructure. The key issue for the applications of SERS is to secure the fabrication technique of a noble metal nanostructured surface. For an SERS-active surface with stability and reproducibility, a Ag nanodot array is fabricated on the ITO glass using a nanoporous alumina mask with uniform through holes. The signal intensity of SERS from methylene blue (MB) adsorbed on the Ag nanodot array showed much stronger scattering than the one from the Ag film of 50-nm thick. The SERS intensity on the Ag nanodot array is consistently enhanced by increased concentration of MB. These results confirm that the Ag nanodot array on ITO glass can be utilized as a stable platform for the sensitive detection of chemical materials based on SERS. (C) The Authors. Published by SPIE under a Creative Commons Attribution 3.0 Unported License. Distribution or reproduction of this work in whole or in part requires full attribution of the original publication, including its DOI.
Keywords: ANODIC POROUS ALUMINA; METHYLENE-BLUE; SILVER NANOPARTICLES; SERS; SPECTROSCOPY; MASK; LITHOGRAPHY; FABRICATION